Use of Artificial Intelligence in General Elections: Comparison of Indonesian and German Regulations - Andi Tenri Sapada; Mohammad Arif (Artes Libres Institutum, 2025)
This study aims to analyze and compare the regulatory frameworks of Indonesia and Germany concerning the use of Artificial Intelligence (AI) in elections, focusing on preventing the potential misuse of AI technologies. The research employs a normative legal methodology, utilizing a statutory approach, a comparative approach, and a conceptual approach. Through a systematic analysis of legal texts and relevant literature, the study examines the strengths and weaknesses of each country's regulatory framework. The findings reveal significant differences between Indonesia and Germany, particularly in terms of data protection, transparency, and oversight mechanisms. Germany's framework, exemplified by the General Data Protection Regulation (GDPR), provides robust safeguards against AI misuse in electoral contexts, emphasizing transparency and accountability. In contrast, Indonesia's regulatory framework is still developing, with significant gaps that leave it vulnerable to AI-driven electoral manipulation. The study concludes with recommendations for Indonesia to strengthen its legal provisions, enhance transparency requirements, and establish independent oversight bodies to safeguard the integrity of its electoral processes. These findings contribute to the broader discourse on AI regulation in democratic contexts, highlighting the importance of adapting legal frameworks to keep pace with technological advancements.